Adaptive Balance in Posterior Cerebellum - Barmack, Neal H.; Pettorossi, Vito Enrico (Frontiers in Neurology, 2021)
Vestibular and optokinetic space is represented in three-dimensions in vermal lobules IX-X (uvula, nodulus) and hemisphere lobule X (flocculus) of the cerebellum. Vermal lobules IX-X encodes gravity and head movement using the utricular otolith and the two vertical semicircular canals. Hemispheric lobule X encodes self-motion using optokinetic feedback about the three axes of the semicircular canals. Vestibular and visual adaptation of this circuitry is needed to keep track of position and motion in space. Visual and vestibular adaptation lies at the core of the maladaptive problems that encompass the syndrome of mal de debarquement. In this review we consider evidence that implicates the posterior cerebellum in postural adaptation. Sinusoidal roll-tilt of an animal about the longitudinal axis for at least 5 min induces compensatory eye movements that persist 10-300 s, when the stimulation is stopped. Sustained horizontal optokinetic stimulation (HOKS) for 2-48 hours induces following eye movements that reverse direction and persist when the rotation is stopped and last several hours (OKAN II). The persistence of OKAN II reveals how the nodulus maintains horizontal eye movements when the head changes orientation with respect to gravity. When the vermal lobules IX-X are lesioned, OKAN II remains horizontal in space during pitch, but not during roll-tilt. MDdS presents primarily in women. Neural substrates within the vestibular complex and posterior cerebellum may also be differentially expressed in males and females. Activity in the medial vestibular nucleus is influenced by neurosteroid estradiol (E2) and dihydrotestosterone (DHT). Another neuropeptide, corticotropin releasing factor (CRF), a peptide in the hypothalamo-pituitary-adrenal (HPA) axis, differentially enhances the female response to stress. Inferior olivary neurons express CRF when activated by HOKS. CRF expression in climbing fibers could differentially alter the adaptability of Purkinje neurons. Transcription of several microRNAs in Purkinje cells is influenced by climbing fiber stimulation caused by sustained HOKS. The transcription of one of these microRNAs, miR335, increases by a factor of 28 during sustained HOKS. miR335 regulates the expression of proteins critical for membrane insertion of the GABAA receptors in Purkinje neurons. Adaptive and homeostatic regulation of vestibulocerebellar circuitry may also contribute to the susceptibility to MDdS.